Motivasi dan Self Management Pasien Diabetes Mellitus Tipe 2 - Agianto; Rahmadanti, Mustika; Diani, Noor (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Diabetes mellitus is a chronic disease indicated by abnormal increase of blood glucose level. Diabetesmellitus requires long-term medical attention and treatment to prevent complication and manage the disease.The risk of complication can be reduced by self-management. The success of self-management hygieneconsiting of nutritional, pharmacology, physical training, blood sugar monitoring and foot care aspects areaffected by the motivation of diabetes mellitus patient. This research was located in Sungai Besar Village,from June to July 2019. The aim of this study was to determine the description of the motivation and selfmanagement of type 2 diabetes mellitus patients. It was a descriptive observational research using nonprobability sampling method with consecutive sampling technique. The instrument was questionnaire with atotal of 101 respondents. Result the study showed that most respondents’ motivation was good (72.3%) andmost respondents’ self-management was good (92.1%). It showed that high motivation was indicated bybehaviors. The motivation of type 2 diabetes mellitus patients encouraged them to do self-management ofdiabetes mellitus. Motivation and self management of type 2 diabetes mellitus patients in Sungai BesarVillage were good. Howover, only 2,0% of respondents dry between of their toes after washing and cleaningthem on the aspect of foot care. This result can be used as a reference for health workers to socialize abouthealth education related to the importance of foot care avoiding foot problems. Diabetes patient wereexpected to have great motivation doing self management.